UTILIZATION OF APPLE PEELS FOR THE PRODUCTION OF PLANT CELL-WALL DEGRADING ENZYMES BY ASPERGILLUS FUMIGATUS MS16 - H. Jalis; A. Ahmad; S. A. Khan; M. Sohail (Journal of Animal and Plant Sciences, 2014)
Apple (Malusdomesticaborkh) is one of the popular fruit with an annual global production of several million tones. The use of apple in food production industry led to the generation of huge waste materials in the form of peels and pomace. Owing to the high amounts of lignocellulosics present in the wastes, these can be served as substrate for the production of plant cell-wall degrading enzymes (CWDE). The present study describes the potential of an indigenously isolated strain of Aspergillusfumigatusto produce plant CWDE using apple peels under submerged as well solid-state fermentation. It was observed that the strain was able to produce higher activity of pectinase and xylanase under both the types of fermentation at 30o as well as at 40oC. While less titers of filter paperase, endoglucanase, b-glucosidase was obtained. However, the production of plant CWDE was influenced when the apple peels were supplemented with carboxymethyl cellulose, xylan, pectin and lactose. Interestingly, a structurally irrelevant substrate, lactose, acted as inducer, particularly for the production of pectinase.
Keywords: Apple peels; Aspergillusfumigatus; Pectinase; Xylanase